Synthesis of 3-Hexyl-4-carboxylic acid-6,7-dimethoxy Isocoumarin - Huo, Jing Qian; Zhang, Zhe; Dong, Hai Jiao; Shi, Jia Mei; Si, He Long; Zhang, Jin Lin (Asian Journal of Chemistry, 2016)
In this work, 3-hexyl-4-carboxylic acid-6,7-dimethoxy isocoumarin was synthesized by the direct method and indirect methods with 3-hexyl-4-cyano-6,7-dimethoxy as the raw material. In the direct method, 3-hexyl-4-cyano-6,7-dimethoxy was directly hydrolyzed into 3-hexyl-4-carboxylic acid-6,7-dimethoxy isocoumarin with the mixture of concentrated sulfuric acid and glacial acetic acid as the reaction solvent. While in the indirect method, 3-hexyl-4-cyano-6,7-dimethoxy isocoumarin was firstly hydrolyzed into 3-hexyl-4-carboxamide-6,7-dimethoxy isocoumarin, which was then hydrolyzed into 3-hexyl-4-carboxylic acid-6,7-dimethoxy isocoumarin. By comparing the two methods, it could be concluded that the direct method had the advantages of simple operation, high conversion rate and no special catalyst, so it was a more ideal method to synthesize 3-hexyl-4-carboxylic acid-6,7-dimethoxy isocoumarin.